The Alli Diet Plan : Your Essential Guide to Success with Alli - Apovian, Caroline M.; Foreword by Foreyt; John P. (Des Moines, Lowa Meredith Books, 2007)
Introduces a weight loss program featuring the over-the-counter drug alli that includes meal plans, recipes, a long-term strategy for keeping the weight off, and a fitness program designed to maximize the results.
Include Index.
Your Essential Guide to Success with Alli.
Keywords: Reducing diets -- Reducing diets - Recipes